Quotas and Voice : Further Considerations. (Policy Papers; Policy Paper ;, 2005)
This paper takes stock of the progress made in quota discussions to date, and examines options for adjustments in quotas or voting power outside of a general quota increase. Section II reviews the status of recent quota discussions, while Section III presents the results of updating the data through 2003. Section IV discusses the options for addressing the distribution of quotas and voting power outside of a general increase in quotas. Section V concludes and poses some issues for discussion.